Building a Web Server as a Business Media for PT Cipta Puja Mandiri - Ramadhani, Nur Kholis; Anwar, Anwar; Aswandi, Aswandi (Politeknik Negeri Lhokseumawe, 2024)
A web server is needed by a company as a medium of information as well as a promotional medium. Web servers are not only for information media but also here the web is used for data storage and streaming media. Web servers can make it easier for employees to get data or send data by uploading and downloading it. This research also discusses the QoS method as a method for measuring network speed. The results of the analysis of the measurement of QoS parameters, network quality during this study, the average value obtained from the results of measuring network speed using the QoS method when performing the upload, download and streaming processes with several scenarios is categorized as very good with the average value obtained Troughput = 11927157 bps, Delay = 0. 929 ms, and Jitter = 0. 931 ms. 931 ms.